ISLAM AND HUMAN RIGHTS WITH SPECIAL REFERENCE TO THE UNIVERSAL HUMAN RIGHTS AND THE CAIRO DECLARATION ON HUMAN RIGHTS - Mwamburi, Adam Hamisi; Fahm, AbdulGafar Olawale (Jurnal Syariah, 2018)
This article discusses the Islam and Human Rights while making significant reference to the Universal Declaration of Human Rights 1948 and Cairo Declaration of Human Rights 1990. It argues that the Universal Declaration on Human Rights (UNDR) 1948 and the Cairo Declaration on Human Rights (CDHR) 1990 in Islam have major differences which cannot be reconciled. The UNDR, for instance, cannot be relied upon by Muslims because of its severe discrepancies and opposition to the Islamic law. The thrust of the article is that the purported universal rights meant for specific people especially the western world and not the whole humanity. Any attempts by a section of Muslim to implement these rights collectively means that they will have to abandon the teachings of Islam at the expense of the secular western values.